2011
DOI: 10.5505/tjod.2011.05902
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors In Epithelial Ovarian Carcinoma: A Reference Institution Experience

Abstract: SUMMARY Aim

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…4,5 In our study abdominal distension was seen in 44.6% of patients, which was followed by abdominal/pelvic pain with a rate of 19.6%, and vaginal bleeding/irregular menstrual cycles was found in 35.7%. In accordance with our study Oge et al 7 also reported abdominal swelling as the most common complaint (59.1%), and the second most frequent complaint was reported as abdominal pain Cancer statistics often use 5-year OS rate to present a better idea of the longer-term outlook for people with cancer. 5 We found that the OS for OC was 94.3%, 66.4%, and 42.8% at 1, 3, and 5 years, respectively.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…4,5 In our study abdominal distension was seen in 44.6% of patients, which was followed by abdominal/pelvic pain with a rate of 19.6%, and vaginal bleeding/irregular menstrual cycles was found in 35.7%. In accordance with our study Oge et al 7 also reported abdominal swelling as the most common complaint (59.1%), and the second most frequent complaint was reported as abdominal pain Cancer statistics often use 5-year OS rate to present a better idea of the longer-term outlook for people with cancer. 5 We found that the OS for OC was 94.3%, 66.4%, and 42.8% at 1, 3, and 5 years, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Some studies reported that increasing age was most strongly associated with poor survival. 9,10,[18][19][20]22 However, in the other studies of Oge et al 7 and Buldanlı et al 11 revealed that age was not was not effected by the age of the patients in OC.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Current results demonstrated that the median (95% CI) follow-up survival time for surviving ASEOC patients was 22 (18)(19)(20)(21)(22)(23)(24)(25) months. This means that, in general, fifty percent of the ASEOC patients survived at least 22 months.…”
Section: The Global Os Of Aseoc Patients (N=253)mentioning
confidence: 97%